Octane Upgrading of TIP Processes by Recycling in a Layered Zeolite 5A/BETA PSA - Silva, José A.C. (2011)
The objective of this work consists in studying the separation mono/dibranched paraffins by cyclic adsorption process using a layered bed of zeolites 5A and Beta (Figure 1). Aspen ADSIM 2006.5 (AspenTech Inc.) was used for numerically solving an adiabatic dynamic model incorporating mass, energy and momentum balance. Model parameters were taken from experimental data reported in the literature 1, 2. Parametric studies were simulated to determine how process performance is affected by purge quantity, 5A-to-Beta ratio, repressurization/blowdown schemes and operating temperature. Figure 2 shows that a combination of zeolites 5A and Beta can produce an octane gain of 1 RON at 523 K comparatively to the conventional TIP3 by reducing the monobranched C6 fraction in the product. Another advantage of this configuration is the possibility to increase the penetration distance because zeolite Beta acts like a “barrier” to the linear alkanes desorbed from zeolite 5A during the cocurrent depressurization step. It was also demonstrated that a slight increase in temperature (20 K) results in a RON benefit of 0.2 points. Several alternatives are provided to improve the performance of the existing TIP processes with this combination of adsorbents.